1997
DOI: 10.1021/ma970630u
|View full text |Cite
|
Sign up to set email alerts
|

Chain Packing and Dynamics in Polycarbonate Block Copolymers

Abstract: Dynamic mechanical-loss spectra at 1 Hz, and dipolar rotational spin-echo 13C NMR spectra at 15.1 MHz, have been obtained for a series of copolymers of polycarbonate made from monodisperse oligomers of Bisphenol A polycarbonate (B X ), alternating (via connecting carbonate linkages) with single units of 3,3‘,5,5‘-tetramethylbisphenol A (T). The mechanical-loss relaxation of B X T suggests cooperative motions in the copolymer glass at T = −100 and −20 °C. The NMR results indicate that no phenylene rings undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 20 publications
2
46
0
Order By: Relevance
“…Moreover, polymer structural modifications or the addition of several additives usually have similar effects on the ring motion seen by NMR, and on the secondary ␥-relaxation seen by MS or DS. 14,17,22,29,33,34 This correlation has strengthened even more the idea of a close relationship between phenylene ring motion and ␥-relaxation. On the other hand, theoretical calculations and molecular dynamics simulations on systems containing phenylene rings qualitatively agree with the type of motions observed experimentally by NMR depending on the time range examined.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, polymer structural modifications or the addition of several additives usually have similar effects on the ring motion seen by NMR, and on the secondary ␥-relaxation seen by MS or DS. 14,17,22,29,33,34 This correlation has strengthened even more the idea of a close relationship between phenylene ring motion and ␥-relaxation. On the other hand, theoretical calculations and molecular dynamics simulations on systems containing phenylene rings qualitatively agree with the type of motions observed experimentally by NMR depending on the time range examined.…”
Section: Introductionmentioning
confidence: 84%
“…Therefore, it seems unlikely to be the origin of the secondary relaxation unless it is cooperatively linked to the motions or is part of the mechanism a͒ Electronic mail: wapcolej@sq.ehu.es causing the relaxations and therefore monitoring them, as has been repeatedly suggested in the literature. 13,[15][16][17][18][19][20][21][22][23][24][25][26][27] NMR studies of the molecular motions taking place in glassy polycarbonates below T g show that the main characteristic motions in these systems consist of -flips of the phenylene rings around the C1C4 axis ͑see Fig. 1͒, oscillations of the ring about the same axis, and some small amplitude main-chain reorientation.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the t and T linkages on the ability of the materials to shear yield can be evaluated when the B x block lengths are kept the same for the two copolymers. Second, in a thorough investigation of the ␥-relaxation characteristics with DMS and solid-state NMR, 14 we found that these two series of copolymers exhibited distinctive differences in their ␥-relaxation behaviors and chain mobility. Their effects on the materials' ability to shear yield can be determined when the brittle-ductile transition (BDT) temperatures of these copolymers are compared.…”
Section: ␥ Relaxation and Mechanical Properties Of Bpa-pc And Polycarmentioning
confidence: 86%
“…As the block length x increases to seven and nine repeat units, the sideband ratios approach that of BPA-PC. 14 DMS studies of (B x t) n (x ϭ 3, 5, 7, 9) and (B x T) n (x ϭ 1, 3, 5, 7, 9) copolymers show that like BPA-PC, all (B x t) n copolymers have low-temperature ␥-relaxation peaks located at approximately the same temperature (Ϫ100°C at 1.0 Hz). As for (B x T) n copolymers, all of them have the peak located around Ϫ20°C, whereas the intensity of the low-temperature peak around Ϫ100°C increases as the block lengths increase.…”
Section: Bdt Temperatures and Molecular Motionsmentioning
confidence: 99%
“…61 PC/PCCD and PC/PCT blends are also well documented in patents and in the open literature. [62][63][64][65][66] Yee and coworkers [67][68][69][70][71][72] published a series of reports on an investigation of the mechanical and structure-property relationships of PC/cycloaliphatic polyester blends and bisphenol cyclohexanedicarboxylate polyesters. They found that the incorporation of 1,4cyclohexanedicarboxylate linkages enabled PC to exhibit ductile yield behavior and reduced the yield stress.…”
Section: Introductionmentioning
confidence: 99%